Factors affecting pineapple market supply in Johor, Malaysia - Jaji, K.; Man, Norsida; Mohd Nawi, Nolila (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Pineapple (Ananas comosus L. Merr.) is a tropical and economic fruit with encouraging market potential in the global market. It is the first crop grown as a commodity crop in Malaysia and raised the country’s position to a very significant level in the world between the late 60 s and early 70 s. However, Malaysian pineapple’s contribution to the global market in the recent time has been experiencing downward trend, resulting to a set-back in its competitiveness. This study aimed to determine factors influencing pineapple market supply in Johor, Malaysia, with objectives of identifying factors affecting pineapple market supply and quantity supplied of pineapple to the market in the study area. Data were collected using a well-structured close ended questionnaire via face-to- face from 170 randomly selected pineapple farmers. The obtained data were analysed using descriptive analysis, exploratory factor analysis, and regression analysis. Six factors identified by exploratory factor analysis as the factors affecting pineapple supply are credit access, pineapple varieties, distance to the market, cost of input, price of pineapples and extension services. The result of regression analysis revealed that, quantity of pineapple supplied to the market was found affected by farming experience, farm size, credit access, pineapple varieties, cost of inputs, price of pineapples, and extension services at 5%, 1%, 1%, 5%, 1%, 5% and 5% significant level respectively. The study recommends the need for designing appropriate intervention mechanisms focusing on the aforementioned factors to improve industry’s performance in the global market and uplift the status of smallholder pineapple farmers.